The Socratic Characteristics of the Torrance Test for Formal Creative Thinking (B) on the students of the university and secondary level in Jeddah city - Seif El Din, Hoda Burhan (Journal of Humanities & Social Sciences, 2017)
The current study aimed at rationing Torrance Tests of Creativity Thinking (Form B) – TTCT- on the secondary stage and university level female students (180 students). It also aimed at studying the differences among the different secondary stages and university level where the validity and reliability significances and scoring procedures could be obtained; especially that the findings revealed that the previous criteria (scales) do not reflect the creativity power any more. Moreover، the responses which used to be considered as “rare” are not so any more, too. Therefore, one of the objectives of this study is to prepare a detailed booklet which explains the test scoring process and show the original and creative responses suitable for our current time. The findings also assured that the test is valid and reliable especially that the significance level was 0.01 in the total mark and sub-dimensions/sections. This indicates the internal consistency of the measurement tool used.
Keywords: Torrance test for formal creative thinking; secondary school; university stage; female students